Application Of Digital Camera Data For Air Quality Detection. - H., S. Lim; MatJafri, M. Z.; Abdullah, K.; AlSultan, Sultan; Saleh, N. M. (2004)
Air pollution problem becomes increasingly critical in this present-day, whether in the developed or developing countries. Air management is one of the important issues in this 21st century. Malaysia is also affected by this problem.